Penggunaan Data Google Trends untuk Peramalan Tingkat Pengangguran Terbuka di Tingkat Nasional dan Regional di Provinsi Jawa Barat - Lisa Widyarsi; Hardius Usman (Seminar Nasional Official Statistics, 2021)
Unemployment rate data is needed by the government as a basis for making and evaluating policies, especially in times of crisis such as the COVID-19 pandemic. However, official statistics produced by BPS show lag time in presentation and limited survey frequency. Therefore, data with more frequency is needed and presented in real-time as a complement to official statistics, by utilizing big data, one of which is the Google Trends Index. This study aims to utilize Google Trends data to predict the Open Unemployment Rate in Indonesia and West Java. This study uses the ARIMAX method with a research period of February 2005-February 2020. The results of this study found that the Google Trends index can be used to predict the Open Unemployment Rate at the national and regional levels in West Java with good accuracy.